Kurangnya Kesadaran Remaja Terhadap Kewajiban Salat dalam Tinjauan Fikih dan Solusinya - Fu’adi, Eka Agustin (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the factors contributing to the lack of awareness among adolescents regarding religious obligations, particularly the performance of prayer (salat), using a library research method. The focus of the study is directed at two main aspects: internal and external factors that influence adolescents’ religious behavior. Internal factors include weak religious understanding, low intrinsic motivation, and underdeveloped self-control. Meanwhile, external factors involve the lack of parental role models, negative peer influence, dominance of digital media, and limited support from social and formal educational environments. Data were collected through literature reviews of primary sources such as the Qur’an, Hadith, and classical Islamic jurisprudence texts, as well as secondary sources like accredited national journals (SINTA), academic articles, and scholarly books. The analysis reveals that the interaction between internal and external factors significantly shapes adolescents’ religious attitudes, and the weakness of one aspect can exacerbate spiritual decline overall. Therefore, a multidimensional approach involving families, schools, and communities is essential to foster consistent and practical religious awareness among youth. This research is expected to contribute to theoretical development in Islamic education and contemporary religious sociology.